2019
DOI: 10.3389/fpls.2019.00166
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Oxidative Stress on Plant Glycolytic and Respiratory Metabolism

Abstract: Reactive oxygen species (ROS) and reactive nitrogen species (RNS) are present at low and controlled levels under normal conditions. These reactive molecules can increase to high levels under various biotic and abiotic conditions, resulting in perturbation of the cellular redox state that can ultimately lead to oxidative or nitrosative stress. In this review, we analyze the various effects that result from alterations of redox homeostasis on plant glycolytic pathway and tricarboxylic acid (TCA) cycle. Most docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 176 publications
(240 reference statements)
2
94
0
Order By: Relevance
“…Interestingly, the phenotype of these mutants is far less severe than that observed following deficiency in expression of ACL (Fatland et al, 2005), suggesting what was previously anticipated, that this route of acetyl-CoA production is less crucial than that of ACL, which recent studies have suggested is closely associated to the activity of the tricarboxylic acid cycle via a thioredoxintermediated approach (Daloso et al, 2015). Indeed, our results combined with previous observations on ACL unexpected overaccumulation of anthocyanins (Fatland et al, 2005), as well as the behavior of central metabolism under oxidative stress, exhibiting reduction on glycolysis and tricarboxylic acid cycle activity (Dumont and Rivoal, 2019), suggest that this may be an alternative route to sustain the synthesis of these antioxidant compounds even under conditions of stress in which the flux of acetyl-CoA from the tricarboxylic acid cycle is reduced.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, the phenotype of these mutants is far less severe than that observed following deficiency in expression of ACL (Fatland et al, 2005), suggesting what was previously anticipated, that this route of acetyl-CoA production is less crucial than that of ACL, which recent studies have suggested is closely associated to the activity of the tricarboxylic acid cycle via a thioredoxintermediated approach (Daloso et al, 2015). Indeed, our results combined with previous observations on ACL unexpected overaccumulation of anthocyanins (Fatland et al, 2005), as well as the behavior of central metabolism under oxidative stress, exhibiting reduction on glycolysis and tricarboxylic acid cycle activity (Dumont and Rivoal, 2019), suggest that this may be an alternative route to sustain the synthesis of these antioxidant compounds even under conditions of stress in which the flux of acetyl-CoA from the tricarboxylic acid cycle is reduced.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, we initially expected to observe an increased flux through the portion of the tricarboxylic acid cycle providing most of the cytosolic pool of acetyl-CoA, namely the export of citrate from the mitochondria and subsequent conversion by cytosolic ATP citrate lyase (ACL; Fatland et al, 2005), in order to compensate for the reduction in acetyl-CoA. The results observed here, however, are more similar to what would be expected from oxidative stress, with an overall reduction of photosynthesis, glycolysis, and the tricarboxylic acid cycle-related metabolites and an increase of photorespiratory related metabolites Gly and glycerate, pyruvate, and Ala (Dumont and Rivoal, 2019). Moreover, it has been shown that plants deficient in ACL activity unexpectedly exhibit a 4-fold increase in anthocyanin Figure 3.…”
Section: Metabolite Profiling Of Transgenic Linessupporting
confidence: 41%
“…Molecular studies indicated that GAPC plays a vital role in this type of stress and the responsive redox signal transduction. GAPC was up-regulated by both osmotic and salt stress [11]. The overexpression of GAPC3 in Oryza sativa affects the expression of a catalase gene OsCatA and then alleviates salt toxicity through the regulation of H 2 O 2 levels [29].…”
Section: Phenotype and Lcgac Expression Analysis Under Salt And Alkalmentioning
confidence: 99%
“…As a housekeeping gene or protein, GAPDH is widely used as a control in real-time polymerase chain reaction (PCR) experiments. However, studies on GAPDH participating in the cellular response to water stress [10], oxidative stress [11] and apoptosis [12] demonstrated that GAPDH was subject to changes in many biological conditions and might be not stably expressed under stress conditions [13]. Therefore, GAPDH as an internal standard should be tailored to the nature of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Under genetic information processing, translation (758) is most enriched followed by folding, sorting and degradation containing 676 proteins. All the proteins involved in these pathways are very important as they are required by the plant for their basic processes like growth, development and response to different pathological conditions etc 6365 . Two classes including “signal transduction” (1, 983) and “membrane transport” (39) are found highly enriched under environmental information processing subcategory.…”
Section: Construction Of a High Confidence Tulsipin (Hc-tulsipin)mentioning
confidence: 99%